Examining Factors Associated With Farmers' Climate-Adaptive and Maladaptive Actions in the U.S. Midwest - Upadhaya, Suraj; Arbuckle, J. Gordon (Frontiers in Climate, 2021)
The U.S. Midwest is a major producer of grain, meat, dairy, eggs, and other major agricultural commodities. It has also been increasingly impacted by climate change-related extreme weather over the last decade as droughts, extreme rains, floods, and, most recently, severe derecho have damaged crops, livestock, and livelihoods. Climate and agricultural scientists and other stakeholders are concerned that without major shifts away from degrading practices toward regenerative systems, long-term sustainability will be compromised. We used cumulative logistic regression to analyze data from a 2020 survey of 1,059 Iowa farmers to examine 1) how farmers are adapting to increasingly variable and extreme weather-related to climate change and 2) whether selected factors were associated with different kinds of adaptive (e.g., increased use of cover crops) or potentially maladaptive (e.g., increased use of pesticides) actions. Our results found that many farmers have been taking adaptive and maladaptive actions. Stewardship ethics, attitudes towards adaptive action, and integration in conservation-related networks were consistent, positive predictors of increases in adaptive practices. On the other hand, faith in crop insurance as a coping strategy, farm scale, and other factors were associated with some maladaptive actions, with several positive predictors of adaptation also being positive predictors of maladaptation, use of pesticides, and drainage in particular. This research contributes to the growing literature on climate risk management and adaptation in agricultural landscapes by providing empirical evidence of the factors related to farmers' adaptative and maladaptive actions.